The Effect of Oral Health Knowledge, Attitude, and Practice on Periodontal Status among Dental Students - Ahmad, Fatemah A.; Alotaibi, Mazen K.; Baseer, Mohammad Abdul; Shafshak, Sanaa M. (European Journal of Dentistry, 2019)
Objectives The primary aim of the current study is to relate oral health knowledge, attitude, and oral hygiene practice with the periodontal condition of both undergraduate and postgraduate dental students.Materials and Methods Data were collected through a combination of self-reported questionnaire and clinical examination. The estimated sample size was 246. Probing depths and clinical attachment loss were measured in interproximal sites, whereas the gingival index was calculated based on Ramfjord teeth. The Centers for Disease Control and the American Academy of Periodontology classification was used for periodontal diagnosis. The subjects were divided into three groups. Group 1 was composed of undergraduate, preclinical dental students, group 2 consisted of undergraduate clinical-year dental students, whereas group 3 included postgraduate residents.Results A total of 296 dental students participated in this study. Significant differences were found among the groups in their oral health knowledge, attitude, and practice scores. Gingival disease was detected among most of the participants (99.2–100%) with significant differences between different educational levels (group 1 = 1.13, group 2 = 1.16, group 3 = 0.96, p-value = 0.001). Sixty percent of dental students were diagnosed with periodontal disease regardless of its severity. A positive correlation was established between oral health knowledge and attitude and oral hygiene practice. In addition, gingival inflammation severity and the severity of periodontal disease showed a positive correlation.Conclusions This study highlighted the need to improve the oral health knowledge, attitude, and practice of dental students. Gingival and periodontal inflammation was highly prevalent among participants.
Keywords: oral health knowledge; oral health attitudes and practice; periodontal status; dental students